Tingkat Kecemasan dapat Mempengaruhi Kualitas Tidur pada Lansia - Risa Putri Fauzika; Cice Tresnasari; R.A. Retno Ekowati (Bandung Conference Series: Medical Science, 2023)
Abstract. As life span increases, this condition more likely result in general health problems or mental health problems, especially in the elderly. Elderly who experience changes in rest habits, both quantity and quality, are said to experience sleep disturbances. One of the causes of sleep disturbances in the elderly is anxiety. Therefore, the purpose of this study was determine the relationship between anxiety levels and sleep quality in the elderly population. The research subjects were the elderly at Baregbeg Health Center in Ciamis Regency in 2022. The sampling technique was purposive sampling and the samples obtained were 99 elderly people. Analysis of the relationship between variables using the Chi-square test. The results showed that the majority of elderly totaled 62 people (62.6%), the sex of the majority of the elderly was male 55 people (55.6%), the anxiety level of the majority of the elderly was moderate anxiety 43 people (43.3%), the sleep quality of the majority of the elderly was categorized as bad by 60 people (60.6%) and showed a significant relationship between the level of anxiety and the sleep quality of the elderly at the Baregbeg Health Center, Ciamis Regency. In conclusion, there is a significant relationship between the level of anxiety and sleep quality the elderly at Baregbeg Health Center, Ciamis Regency. Suggestions are used as material for consideration for the elderly in order to reduce poor sleep quality and reduce or stop smoking besides that the elderly are expected not to be anxious and depressed. Abstrak. Seiring bertambah panjangnya usia hidup, kondisi ini lebih cenderung mengakibatkan masalah kesehatan secara umum atau masalah kesehatan mental, khususnya pada lansia. Lansia yang mengalami perubahan kebiasaan istirahat, baik kuantitas maupun kualitas, dikatakan mengalami gangguan tidur. Salah satu penyebab gangguan tidur pada lansia yaitu kecemasan. Maka dari itu, tujuan dari penelitian ini adalah mengetahui hubungan antar tingkat kecemasan dan kualitas tidur pada populasi lansia. Subjek penelitian yaitu lansia di Puskesmas Baregbeg Kabupaten Ciamis tahun 2022. Teknik penentuan sampel Purposive sampling dan sample yang diperoleh 99 lansia. Analisis hubungan antar variabel menggunakan uji Chi-square. Hasil penelitian menunjukan umur lansia mayoritas 60-65 tahun berjumlah 62 orang (62,6%), jenis kelamin lansia mayoritas laki-laki 55 orang (55,6%), tingkat kecemasan lansia mayoritas kecemasan sedang 43 orang (43,3%), kualitas tidur lansia mayoritas dikategorikani buruk 60 orang (60,6%) dan hasilnya menunjukan hubungan signifikan antar tingkat kecemasan dan kualitas tidur lansia di Puskesmas Baregbeg Kabupaten Ciamis. Simpulan adanya hubungan yang signifikan antar tingkat kecemasan dan kualitas tidur lansia di Puskesmas Baregbeg Kabupaten Ciamis. Saran dijadikan bahan pertimbangan lansia agar mengurangi kualitas tidur yang buruk dan mengurangi atau berhenti merokok selain itu lansia diharapkan tidak cemas dan depresi.